Mesoporous Mn3O4 coated reduced graphene oxide for high-performance supercapacitor applications. (22nd October 2018) - Kuila, Biplab Kumar; Zaeem, Shaikh Mohammed; Daripa, Soumili; Kaushik, Kanak; Gupta, Saral Kumar; Das, Santanu
Abstract: We report the facile synthesis of mesoporous Mn3 O4 coated reduced graphene oxide (rGO) nanocomposite using a simple low temperature wet chemical process and demonstrated the nanocomposite material as high-performance electrodes for electrochemical supercapacitor. The nanocomposite structure is unique as it consists of an ultra-thin, mesoporous (pore size ∼1.9–2.6 nm) with oriented pore size of Mn3 O4 layer deposited on the surface of rGO. The structure and the orientation of nanopores in the Mn3 O4 layer were further confirmed using HRTEM, while structural and morphological analysis were carried out using XRD, Raman spectroscopy, SEM, TEM, and SAED. The pore size and the pore distributions were verified using BET surface area technique, which demonstrated the nanocomposite exhibits uniform distribution of pores of dimension ∼1.9–2.6 nm throughout. The electrocatalytic behavior of the nanocomposite was found to be ideal for their use as supercapacitor electrodes as high-performance charge storage devices. Finally, we demonstrate the supercapacitor electrode using Mn3 O4 -rGO nanocomposite followed by their electrochemical characterizations for electrocatalytic activity for charge storage. The hybrid material shows best capacitance value of 221 F g −1 at current density 0.15 A g −1 with good cycling stability. We believe that our investigations will pave a pathway towards various new applications, including, electrochemical catalysis, sensing, energy harvesting and storage and many more.